Differences in the proteomic profiles of the eutopic endometrium in patients with internal and external adenomyosis. - Marta Valdés-Bango; Mikel Azkargorta; Meritxell Gracia; Cristina Ros; Mariona Rius; María-Angeles Martínez-Zamora; Cristian De Guirior; Lara Quintas; Félix Elortza; Francisco Carmona (PLOS Global Public Health)
Two separate phenotypes of adenomyosis have been recognized, determined by the anatomical position of the adenomyotic lesions within the myometrium. This suggests that adenomyosis impacting the inner myometrium and that affecting the outer myometrial layer may have distinct origins and display different clinical and radiological characteristics. We aimed to investigate the endometrial proteomic profiles of patients with both adenomyosis phenotypes to identify differentially expressed proteins and molecular pathways, shedding light on their distinct pathogenic mechanisms. We conducted a cross-sectional study that included thirty-six participants (nine with internal adenomyosis, nine with external adenomyosis, and eighteen healthy controls based on sonographic criteria) from September 2021 to September 2022. Endometrial samples were collected and processed for proteomic analysis. Mass spectrometry and a Data Independent Acquisition strategy were used to identify differentially expressed proteins. Gene Ontology and Ingenuity Pathway Analysis were employed for further functional analysis and network generation. The proteomic profiles of the eutopic endometrium differed significantly among women with internal adenomyosis, external adenomyosis, and controls. Biological functions related to the innate immune response were affected by differentially expressed proteins in patients with both phenotypes of adenomyosis compared to controls. The proteomic profiles of the endometrium of women with external versus internal adenomyosis exhibited significant differences, with external adenomyosis showing a heightened immune response and inflammatory activity, while internal adenomyosis was associated with altered signaling pathways related to cell migration and apoptosis. Upstream regulator analysis predicted the activation of inflammatory mediators like LPS, TGF-β1, IL-4, and IFN-γ in external adenomyosis, and MAPK1 and IRF2BP2 along with multiple microRNAs in internal adenomyosis. Overall, our findings support distinct pathogenic mechanisms for the two adenomyosis phenotypes, highlighting the need for further research to explore their implications for diagnosis, correlation with symptoms, and new potential therapeutic strategies.